Physical and Spatial Characteristics of Slum Territories Vulnerable to Natural Disasters - (:unkn) unknown (My University, 2011)
The purpose of this paper is to explain how, in developing countries, the poor have creatively appropriated risky areas where urban settlement is prohibited, resulting in territories rich in organic and unique forms, adapted to the morphological territorial conditions (slope, height, profile) and to different risk situations. In this context, it is important to present the physical and spatial characteristics of slum territories taking into consideration the ways in which they are appropriated, presented, either in a "visible" or "hidden" manner in the urban landscape as well as locating them in a territory (outskirts or urban perimeter). Subsequently, the current urban forms shall be analysed, using irregular grid configurations, in corridors, terraces, etc., as developed by slum residents in response to the demands and topography of steep terrain. In order to achieve this, several slum cases shall be referred to in: East London (South Africa), Salvador de Bahia (Brazil) and Lima (Peru). Finally, the key points analysed within this article shall be presented briefly.
Keywords: African Research